Relevansi Konsep Pemikiran Ekonomi Islam Yusuf Qardhawi dan Penerapannya di Indonesia - Nora Maulana; Zulfahmi Zulfahmi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The low level of public literacy related to Islamic economics causes errors and mistakes in the practice of Islamic economics, so that if it is ignored it can have a negative impact on the development and progress of Islamic economics itself. So it is important for various parties to know and study various models of economic thought concepts from Islamic economists such as Yusuf Qardhawi. Because the concept of Islamic economic thought can be used as a reference in dealing with economic problems. Yusuf Qardhawi's phenomenal economic thought is related to professional zakat, ethics and economic norms which include the ethical concepts of production, distribution, and consumption. Not only that, but Yusuf Qardhawi also expressed his phenomenal thoughts related to the concept of property which includes zakat, taxes, interest and usury, the concept of working in Islam, government involvement in economic ethics, and also the concept of equitable distribution of welfare for all people. Although it contains various pros and cons, the journey of professional zakat in Indonesia has attracted a lot of attention from various groups ranging from academics, scholars and the government who are also serious about responding to this phenomenon, especially MUI with the issuance of Law No. 3 of 2003 concerning Income Zakat, Law No. 23 of 2011 concerning Zakat Collection, PMA and BAZNAS also participate to strengthen regulations and policies on professional zakat regulation. Keywords: Relevance, Islamic Economics, Yusuf Qardhawi, Indonesia.